PENGARUH LEVERAGE DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL INTERVENING (Studi kasus pada perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia periode 2012-2016) - Ramadhani, Ridho; Akhmadi, Akhmadi; Kuswantoro, Muhammad (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2018)
This study aims to examine the effect of leverage proxyed by Debt to Equity Ratio (DER) and profitability proxy with Return On Assets (ROA) to company value proxy with Price to Book Value (PBV) through dividend policy proxy with Dividend Payout Ratio (DPR) as an intervening. The study was conducted on 37 manufacturing companies using multiple regression analysis with the help of SPSS version 19.00. The result of the research shows that leverage has significant positive effect to company value; profitability has a significant positive effect on firm value; leverage has no effect on dividend policy; profitability has a positive effect on dividend policy and dividend policy has a positive effect on firm value. The dividend policy can’t mediate the indirect effect between leverage and profitability on firm value.